Analysis of Prepositions in Surah Maryam - Supriyadi, Moh.; Afifurrahman, Afifurrahman (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Surah Maryam, which is the nineteenth Surah in the Quran. This Surah consists of ninety-eight verses and belongs to the Meccan Surah group because most of the verses were revealed before the Prophet Muhammad moved to Medina and even before his companions migrated to the distant lands. A letter is what indicates a meaning in something else. It is divided into three types: a letter specific to a noun, such as a preposition; letters that make a noun nominative and a verbal noun accusative; and a letter shared between nouns and verbs, such as conjunctions and interrogative letters. The aim of this study is to analyze the letter jar in Surah Maryam. The research method This research is some of the types of library research, what is meant by library research is the research that the researcher works in the library or outside it for all the facts or data from the types of books. The result of the prepositions in Surah Maryam is seventy-five letters and the prepositions are as follows: Ba, Min, An, Ali, Fi, Lam, and as for the types of prepositions, the researcher found in Surah Maryam as follows. The letter Ba has nineteen letters from thirty-four letters to three letters The letter Lam has four letters The letter An has two letters The letter Ali has eight letters The letter Fi has thirteen letters